ANALISIS PRAKTEK-PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP KEPUASAN KARYAWAN DAN KINERJA INOVASI KANTOR POS PUSAT YOGYAKARTA - Herlinda Rachman (Among Makarti, STIE AMA Salatiga, 2019)
This study aims to find out how to improve the performance of Yogyakarta Central Post Office employees. To find out the importance of compensation to the performance of the Yogyakarta Central Post Office. To find out the importance of job satisfaction on performance, the Central Yogyakarta Post Office. To find out the importance of HR practices regarding training, compensation and simultaneous job satisfaction on the performance of Yogyakarta Central Post Office Employees. The variables of this study are training, compensation, job satisfaction and innovation performance. The population in this study is the Central Yogyakarta Post Office employees totaling 230 people, so the number of samples is x 5 (26 x 5) = 132 employees. Stratafied Random Sampling Technique. The method of data collection uses a questionnaire. The analysis technique used is multiple linear regression with a significance level of 5%. The results of the research obtained by the training are not expected to achieve innovation. No significant compensation for innovation performance. Satisfaction of positive and significant decisions on innovation performance. Positive and significant compensation for job satisfaction. Training, Compensation and Job Satisfaction positively and significantly towards innovation performance. Improved training performance, compensation and job satisfaction by 27.3%, while the remaining 72.7% requirements for other factors. Keywords: Training, Compensation, Job Satisfaction and Innovation Performance